The Dominant Role of Consumer Perception in Urban Farming Housing Purchase Intention - Zulfikar Zulfikar; Muhammad Novrizal Ramadhan; Fahrian Arsyam Gulthom (Universitas Negeri Makassar, 2026)
Urban farming housing has emerged as an innovative approach to address urban environmental challenges and limited green spaces in rapidly growing cities such as Makassar, Indonesia. Despite its potential, consumer acceptance of this housing concept remains relatively low. This study aims to analyze the influence of knowledge, perception, and attitude on consumer purchase intention toward urban farming housing in Makassar. A quantitative approach was applied using survey data collected from 202 respondents. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that knowledge significantly affects perception (β = 0.362, p < 0.01) but does not significantly influence attitude or purchase intention. Perception, on the other hand, significantly affects both attitude (β = 0.797, p < 0.01) and purchase intention (β = 0.622, p < 0.01), making it the most dominant factor in the model. Meanwhile, attitude does not have a significant influence on purchase intention (β = 0.204, n.s.), indicating that consumers' behavioral decisions are not solely shaped by positive attitudes. These findings differ from the assumptions of the Theory of Planned Behavior (TPB), suggesting that perception plays a more decisive role in explaining purchase intention than attitude. This study contributes to the literature by providing empirical evidence that challenges the conventional TPB model in the context of sustainable housing. Practically, the findings suggest that housing developers should focus on enhancing consumer perception through environmental education, experiential marketing, and sustainability-based branding strategies.